The misuses of sustainability: adult education, citizenship and the dead hand of neoliberalism - Holford, John (Springer, 2016)
‘‘Sustainability’’ has a captivating but disingenuous simplicity: its meanings are complex, and have political and policy significance. Exploring the application of the term to adult education, this paper argues that a particular discourse of ‘‘sustainability’’ has become a common-sense, short-circuiting critical analysis and understanding of policy options. This ‘‘business discourse’’ of sustainability, strongly influenced by neoliberal ideas, encourages the presumption that educational programmes and movements which have died out were unsustainable, bound to fail, and even responsible – having failed to adapt – for their own demise. Potentially valuable experience is thus excluded from the educational policy canon. The author uses three cases from 20th-century adult education, namely (1) English liberal adult education; (2) ‘‘mass education’’, also known as community development, in the British colonies; and (3) UNESCO’s Fundamental Education, to challenge this presumption. He demonstrates for each case how a business discourse has implied their ‘‘unsustainability’’, but that the reality was more complex and involved external political intervention.